ANALYTICAL TOOLS FOR CONSULTING COMPANY’S DEVELOPMENT STRATEGY FORMATION: SELECTION AND OPTIMIZATION (International Journal of Innovative Technologies in Economy, 2021)
In this paper the different analytical methods of strategic management were summarized as one analytical stage of the whole strategy formation process. The best practice of managers which was described in different research was reviewed and developed in terms to get more quick and suitable management tools for small and medium sized consulting companies. SWOT-analysis was used to estimate basic quality factors, which influence on the company. EFAS, IFAS, SFAS methods were used and supplemented by adding the reference data for consulting companies. Visualization with using a bubble chart was proposed for EFAS, IFAS, SFAS results interpretation with the possibility of considering company’s dynamic changes. The stakeholders’ analysis was proposed to use as a part of analytical stage of development strategy formation process for consulting companies. This type of analysis was improved by using the 5-scored scale estimation as a risk-management tool. That would help to build a stakeholders’ map for further visualization. As a result, the level of strategy objectiveness will be increased, total spent time will be decreased and the strong analytical background for further strategy formation process will be achieved.